Local Capacity, Village Governance, and Livelihood Development: A Review - Prakoso, Maliki Aji; Fadli, Amril; Abd Fatah, Rahmat; Mardhotillah, Bunga; Prananingrum, Dwi Kartika; Feriana, Rina; Ariyanto, Komang (Universitas Pahlawan Tuanku Tambusai, 2025)
This article reviews the literature on the relationship between local capacity, village governance, and livelihood development at the village level. It aims to explore how local capacity enhances village governance and its subsequent effect on the livelihoods of community members. The review analyzes previously published scholarly articles on the subject. The findings reveal that robust local capacity is positively correlated with more effective village governance, which, in turn, promotes sustainable livelihood development. Additionally, the article identifies key factors influencing this relationship, including community participation, program sustainability, and government policy support. In conclusion, the article emphasizes the importance of strengthening local capacity and enhancing village governance as strategies for fostering sustainable livelihood development. The insights from this literature review are intended to guide policymakers and practitioners in designing more effective village development programs.